The Influence of Financial Literacy and Socio-Demographics on the Financial Management Behavior of Migrant Students in Surabaya - Cynthia, Angelina; Linawati, Nanik (Economic Education and Entrepreneurship Journal, 2024)
This research aims to analyze the influence of financial literacy and sociodemographic characteristics on the financial management of migrant students in Surabaya. We employed a quantitative descriptive approach and collected data through a shared Google Form. The analysis was conducted using Stata software. The results of our research reveal that a higher level of financial literacy has a positive and significant impact on the financial management abilities of migrant students. However, sociodemographic factors such as age, gender, and income do not exhibit a significant influence on their financial management. This analysis provides valuable insights into the significance of enhancing financial literacy among migrant students, thereby assisting them in improving their financial management skills.Keywords: Financial Literacy, Financial Management BehaviourDOI: http://dx.doi.org/10.23960/E3J/v7i1.13-17